4+2q-(3q+9)-(5q+8)=

Simple and best practice solution for 4+2q-(3q+9)-(5q+8)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4+2q-(3q+9)-(5q+8)= equation:


Simplifying
4 + 2q + -1(3q + 9) + -1(5q + 8) = 0

Reorder the terms:
4 + 2q + -1(9 + 3q) + -1(5q + 8) = 0
4 + 2q + (9 * -1 + 3q * -1) + -1(5q + 8) = 0
4 + 2q + (-9 + -3q) + -1(5q + 8) = 0

Reorder the terms:
4 + 2q + -9 + -3q + -1(8 + 5q) = 0
4 + 2q + -9 + -3q + (8 * -1 + 5q * -1) = 0
4 + 2q + -9 + -3q + (-8 + -5q) = 0

Reorder the terms:
4 + -9 + -8 + 2q + -3q + -5q = 0

Combine like terms: 4 + -9 = -5
-5 + -8 + 2q + -3q + -5q = 0

Combine like terms: -5 + -8 = -13
-13 + 2q + -3q + -5q = 0

Combine like terms: 2q + -3q = -1q
-13 + -1q + -5q = 0

Combine like terms: -1q + -5q = -6q
-13 + -6q = 0

Solving
-13 + -6q = 0

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '13' to each side of the equation.
-13 + 13 + -6q = 0 + 13

Combine like terms: -13 + 13 = 0
0 + -6q = 0 + 13
-6q = 0 + 13

Combine like terms: 0 + 13 = 13
-6q = 13

Divide each side by '-6'.
q = -2.166666667

Simplifying
q = -2.166666667

See similar equations:

| 75=6v | | 2(c+x)=3x | | x/2=13x | | n/.f=n/81 | | 1200x+500=24 | | 4x-17=-45 | | 8x^3-2x+24=0 | | 4(3a-4)=4(5a-20) | | -4/32= | | 4(k-1)+3=2(k+5) | | 68+46+12-6=180 | | 1.5x-5.5=3/2x-1.2 | | 3/4*x=1/8 | | 3b+n=30 | | -1/4c=-20 | | sqrt(3x+19)-sqrt(x+2)=3 | | 1.5x-0.5=3/2x-1.2 | | 28/25--20= | | 2.2x+3.5=3y | | 2x-3/2=0 | | (x-4)^3/2 | | 86+2x=400 | | 0.07z+0.22=-0.41 | | 3x=2a-5b | | 3/4×12=9 | | -2(x-3)=-9(6-4x) | | 13-n/8 | | 2a-5b=3x | | 28/4*25-4= | | 1.75h+4=18 | | W-n/8 | | 3tan^2x+5tanx+2=0 |

Equations solver categories